Protection of public decency in Polish criminal law of the pre-Partition period against conduct classified today under Article 140 of the Petty Offences Code (Ius Novum, 2020)
The article presents the issues related to the protection of public decency against conduct currently classified as indecent antics (Article 140 of the Petty Offences Code) in the period until Poland lost its independence in the 18th century. The regulations in force at that time have been analysed, along with the factual cases examined by the courts.
Keywords: public decency; indecent antic; municipal criminal law; rural criminal law